Peningkatan Literasi Keuangan Melalui Adopsi Qris sebagai Solusi Pembayaran Digital di Desa Kineppen Kabupaten Karo - Muhd. Aidil Fitri; Sri Adel Febri Aldina; Adrian Niken Lubis; Benni Icshanda Rahman; Nurbaiti Nurbaiti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Current technological advances have had a significant impact on various aspects of life, especially in the economic sector. Through this Community Service Program (KKN), the aim is to improve understanding and literacy of digital finance in Kineppen Village, Munte District, Karo Regency, by adopting the use of QRIS or Quick Response Code Indonesian Standard. The current situation in the village shows a severe lack of understanding and literacy in digital finance, driven by a payment system that still relies on cash and the disparity in technology use in the village. In this community service program, students carried out several stages, namely preparation, outreach, program planning, implementation, monitoring, and evaluation. The results of the work program show that MSME actors have fully understood and adopted QRIS in their lives, especially in the payment system, and that the community is interested in making non-cash payments using QRIS rather than cash payments. This activity shows that digital transformation in a small village can bring about change and enable MSMEs to become one of the creative economies that can prosper in the current digital era.